An adaptive power control method for soft open points based on virtual impedance - Li, Yan; Li, Yang; Zhao, Xingjian; Gao, Feng; Xu, Tao (Frontiers in Energy Research, 2024)
The fluctuations in power output from distributed power sources are rapid and dramatic, causing voltage fluctuations in the distribution network that threaten the safety of electricity consumption. Soft open points (SOPs) can replace traditional contact switches and are expected to suppress voltage fluctuations. However, traditional power regulation methods based on the reference values are unable to address rapid and large voltage fluctuations. Therefore, this paper proposes an adaptive power control method for SOPs based on virtual impedance. The SOP is modeled as a series link of adjustable impedance and a voltage source. Then, the voltage difference component is used to calculate the reference for the DQ domain to regulate the power flow in real time automatically. By doing so, the proposed method can smooth the voltage fluctuations in the distribution network. Additionally, the virtual impedance is also optimized to minimize the power loss. Finally, the method is validated through simulation and experiments, demonstrating that this method can automatically regulate power and significantly reduce voltage fluctuations.